Effects of Maternal Supplementation With Omega-3 Precursors on Human Milk Composition. (May 2017) - Mazurier, Evelyne; Rigourd, Virginie; Perez, Paul; Buffin, Rachel; Couedelo, Leslie; Vaysse, Carole; Belcadi, Wafae; Sitta, Rémi; Nacka, Fabienne; Lamireau, Delphine; Cambonie, Gilles; Picaud, Jean-Charles; et al.
Background: Long-chain polyunsaturated fatty acids (LC-PUFAs) are important for newborn neurosensory development. Supplementation of breastfeeding mothers' diets with omega-3 PUFAs, such as alpha-linolenic acid (ALA), may increase their concentration in human milk. Research aim: This study aimed to assess human milk composition after 15-day supplementation regimens containing either omega-3 PUFAs or olive oil, which does not provide ALA. Methods: A multicenter factorial randomized trial was conducted with four groups of breastfeeding women, with each group containing 19 to 22 women. After a 15-day ALA washout period, three groups received supplementation with omega-3 precursors for 15 days: an enriched margarine (M), a rapeseed oil (R), and a margarine and rapeseed oil (MR). The fourth was unexposed to omega-3 precursors (olive oil control diet, O). After 15 days, blind determination of human milk fatty acid (FA) composition was assessed by gas chromatography, and the FA composition was compared among groups using variance analyses. Results: Alpha-linolenic acid content, expressed as the mean (standard deviation) total human milk FA percentage, was significantly higher after diet supplementation with omega-3 PUFAs, with values of 2.2% (0.7%) (MR), 1.3% (0.5%) (R), 1.1% (0.4%) (M), and 0.8% (0.3%) (O at D30) ( p < .003 for each comparison). The lowest LA–ALA ratio (5.5) was found in the MR group ( p < .001). Docosahexaenoic acid and trans FA concentrations did not differ among groups. Conclusion: In lactating women, omega-3 supplementation via the combination of enriched margarine and rapeseed oil increased the ALA content of human milk and generated the most favorable LA–ALA ratio for LC-PUFA synthesis.